¿Es posible la admisión de medios probatorios y/o argumentos luego del cierre de los requerimientos? Breves notas con motivo de la aplicación del reglamento del procedimiento de fiscalización tributaria - Bardales Castro, Percy (2013)
The object of the principle of material truth is to assure the certainty of facts in order to be able to issue a ruling as close to reality as possible. The principle has an intimate relationship with the limitation periods which, as regulated in our Tax Code, are only established as minimum terms in which the tax debt or has to comply with the administration’s requirements, without specifying any maximum. The author explains how it is that the terms regarding the presentation of documents have to be fixed considering the civilian’s interestand not against it. He affirms that, as long as the collection procedure of a certain period has not concluded, the debtor has the faculty to offer information and arguments to the administration in order to sustain his statement, allowing him to discuss the objections formulated against him.